INNOVATIONS IN EDUCATIONAL SUPERVISION TO SUPPORT THE IMPLEMENTATION OF DIGITAL BASED LEARNING - Darimus Darimus (Penelitian dan Pengembangan Ilmu, 2025)
This study explores how innovations in educational supervision practices can facilitate the effective implementation of digital-based learning in schools.narrative review, this study synthesizes theoretical and empirical findings from international literature published between 2015 and 2025. The results of the analysis identified four main themes, namely: (1) a transformational shift in the role of supervision towards digital mentoring and facilitation functions; (2) integration of technology-based supervision tools such asLMS analytics, video-based observation, and artificial intelligence-based feedback; (3) the role of supervisory innovation in improving teachers' digital competence through coaching and reflection; and (4) the importance of institutional and policy support in building a sustainable digital supervision ecosystem. These findings confirm that digital educational supervision requires technological readiness accompanied by transformational leadership, a collaborative culture, and systemic policy alignment. This study also proposes a conceptual modelDigital Educational Supervision Innovation Framework (DESIF)as a basis for future empirical research and policy formulation.